PENGARUH PEMANASAN DAN PENGERINGAN DAGING BUAH KELAPA TERHADAP ASAM LEMAK BEBAS PADA PEMBUATAN TEPUNG KELAPA (THE IMPACT OF HEATING AND DRYING OF COCONUT TOWARDS FATTY ACID IN COCONUT POWDER PRODUCTION) - Santoso, Hadi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
The Coconut has an important role in the economy and also in providing nutrition. The coconuts flesh is the most utilized part to be processed as coconut powder. Turning coconut flesh into coconut powder is one way to preserve coconut by reducing its fat content. Coconut powder is used in making cakes, coconut milk, as well as bread flavor. Hence, the powder should be visually white in color and have a specific coconut aroma. The research was performed using the split plot design consisting two factors: A, the heating factor (A1, A2 and A3) and B, the drying factor (B1 and B2). Coconut powder processing undertook several stages namely the cleaning of coconut skin and shell, washing, heating, grating, drying, steaming, re-drying, and grinding. Heating and drying are two determining steps in the process as to stop the activities of damage causing enzyme and prevent microbial growth. In the production of coconut powder, heating is done by steaming at the temperature of 80 - 90 C and drying using a drier to reduce the fat content to 0.29%. The coconut powder will become white in color and with a specific coconut aroma.